TINGKAT PENGETAHUAN TENTANG BAHAYA MEROKOK PADA SISWA KELAS VI SEKOLAH DASAR NEGERI 56 BANDA ACEH - Emiralda Emiralda; Meri Lidiawati (Jurnal Sains Riset, 2021)
Smoking is an activity that often be done by society.Smoking behavior is not only happening in adults but has penetrated into adolescents and even schoolstudents. Smoking means burning tobacco and tar leaves and sucking the smoke itproduces. This study aims to determine the level of knowledge about the dangers ofsmoking in the sixthgrade students of elementary school 56 Banda Aceh in 2017.The research is a descriptive research with cross-sectional approach. The sample is54 students of class VI elementary school 56 Banda Aceh determined by totalsampling technique. Data collection was obtained by distributing questionnaires. The results showed that the level of knowledge about the dangers of smoking in thesixth grade students of elementary school 56 Banda Aceh in 2017, ie high category of45 respondents (83,3%), quite high as many as 5 respondents (9,3%), low as much 4respondents (7,4%) and very low amounted to 0 respondents (0%). Based on theresearch results can be concluded that the level of knowledge about the dangers ofsmoking is in the high category that is 83,3% of the totalrespondents.Keywords: Knowledge about the danger of smoking